Model Model Manajemen Strategi Dalam Pengembangan Kampung Tematik Di Kota Tangerang - Muttaqijn, Muhammad Imam; Yulistyono, Agus; Hendriana, Didin (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2024)
Background – The results of the prior assessment of thematic villages by the Tangerang City Government have not found maximum results, because thematic villages that are included in the main cluster are still below fifty percent. This shows that the performance of thematic village organizations still needs to be improved. Aim – This study aims to find a management strategy model in developing thematic villages in Tangerang City. Thematic villages have the opportunity to support the development of Tangerang City through good strategic management. Design / Methodology / Approach – The approach used in this research is qualitative. The object of research is thematic villages in Tangerang City. Informants are the leaders of thematic villages, the determination of informants is done purposively, using purposive sampling technique. Data collection techniques used observation, interview documentation and triangulation. Data analysis using the Miles and Huberman model, namely data reduction, data presentation and conclusion drawing. Findings – This study show that most thematic villages in Tangerang City have not used a strategic management model in developing thematic villages in the form of determining a vision, conducting an environmental assessment, setting goals and implementing strategies. Conclusion – Institutional strengthening needs to be carried out through the implementation of a management strategy model assisted by the Tangerang City Bappeda. Research Implication – The implications of this study, with the results of the study in the form of a strategic management model can be used as input for the development of management science. Limitations – with a qualitative approach, the research results cannot be generalized. So for areas that have different characteristics from Tangerang City, more in-depth research is needed. But with this research, a strategic management model will be found in the development of thematic villages.